P1412 A new light to improve the view of the anatomical details during micro-invasive trans-ventricular repair of degenerative prolapse of mitral valve. (17th January 2020) - Vairo, A; Marro, M; Speziali, G; Rinaldi, M; Salizzoni, S
Abstract: BACKGROUND: Mitral valve repair is the preferred surgical treatment for severe mitral regurgitation due to degenerative leaflet prolapse. Within the growing era of transcatheter treatments for valvular heart disease, an innovative micro-invasive trans-ventricular beating-heart procedure was developed. Three-dimensional (3D) transoesophageal echocardiographic guidance is crucial to assist the operator in instrument navigation and chords positioning. 3D ultrasound technology is constantly evolving and a special light, that can be mobilized within the 3D images, has recently been invented. This light allows to illuminate the structures from different points of view and increase the definition of the anatomical details. PURPOSE: To show the advantages of this new 3D image analysis technology, described above, through a sequence of intra-procedural images of a mitral valve repair by trans-ventricular polytetrafluoroethylene (ePTFE) chords implantation. METHODS: The procedure is performed using a device that is introduced through a posterolateral ventriculotomy and it is advanced towards the mitral valve under real-time 3D transoesophageal guidance. The prolapsing segment, in this case central part of posterior leaflet (Fig. 1 A, B and C), is grasped with the jaw of the instrument (J in Fig. 1D), then the chords are implanted, tensioned and secured outside the ventricle. Figure 1A shows the pre-operative image of posterior leaflet prolapse with flail (P2 segment) and the light illuminates the valve from above. The broken chords (arrow in Fig. 1A) can be recognized with high definition. The light can also be placed on the valve plane (Fig. 1B) or below (Fig. 1C). When illumination occurs from the left ventricular side, the coaptation loss due to the P2 flail is highlighted (arrow in Fig. 1C). After placement, tensioning and securing the chords outside the ventricle, the prolapse disappears and the correct coaptation is re-established (Fig. 1E). The coaptation deficit is no longer visible, even with the light placed below the valve and it is possible to see the light coming out of the aortic valve (Ao), opened in systole, with mitral valve closed (Fig. 1F). RESULTS: At the end of the procedure the residual mitral regurgitation was trivial and no loss of coaptation can be evidenced even with the light placed in the left ventricle (Fig. 1F). CONCLUSIONS: This new light allows to improve the anatomical definition of 3D echocardiographic images, allows better visualization of the coaptation defects and can be used as a further verification of the result especially in cases of micro-invasive mitral repair.